Case report: Indocyanine green fluorescence-guided imaging in laparoscope, a more sensitive detection technique of lateral lymph nodes metastases from rectal neuroendocrine tumors - Zhang, Yueyang; Zhang, Yi; Yang, Yi; Xu, Zheng; Gao, Changyuan; Liu, Meixi; Zhu, Wenjia; Zhao, Hong; Zhou, Haitao (Frontiers in Oncology, 2022)
Background: The diagnosis and surgical strategy of lateral lymph node metastases of rectal neuroendocrine tumors are still controversial. At present, the major diagnostic means rely on imaging examinations, but will be affected by the size of lymph nodes leading to false negativity. We provide a new technique to determine lateral lymph node metastases during surgery. Clinical case: A 68-year-old man developed abdominal pain, bloating and fever for a month. Colonoscopy revealed the mass is 2.4 cm x 2.0 cm in size, with a wide stratum, poor mobility, and a rough but intact surface mucosa. Therefore, rectal neuroendocrine tumors(R-NET) were diagnosed. Multiple imaging methods, such as CT, octreotide imaging and endoscopic ultrasonography, have not found lateral lymph node metastases from rectal neuroendocrine tumors. But indocyanine green (ICG)-enhanced near-infrared fluorescence-guided imaging during surgery found left lateral lymph nodes metastases, which was proved by postoperative pathological examination. Conclusions: We believe that applying ICG-enhanced near-infrared fluorescence-guided imaging in laparoscope can improve the detection of positive LLNs in those R-NET patients who did not reveal LNM on imaging examinations.